2016
DOI: 10.2341/15-320-l
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Endodontically Treated Teeth Restored With Bulk Fill, Bulk Fill Flowable, Fiber-reinforced, and Conventional Resin Composite

Abstract: The fracture resistance values of endodontically treated teeth restored with either bulk fill/bulk fill flowable or fiber-reinforced composite were not different from those restored with conventional nanohybrid resin composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
73
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 34 publications
10
73
3
5
Order By: Relevance
“…Kikuti et al revealed that the combination of Single Bond/P60 composite resin was capable of recovering the fracture resistance of premolars with MOD cavities, while silorane adhesive/silorane composite resin could not . The important role of adhesive system in fracture strength of the restored teeth was confirmed by these authors so that Single Bond as a filled adhesive is able to create a thick adhesive layer, acting as a stress absorbent . Furthermore, this layer resulted in more even distribution of stresses induced by polymerization shrinkage and load testing .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Kikuti et al revealed that the combination of Single Bond/P60 composite resin was capable of recovering the fracture resistance of premolars with MOD cavities, while silorane adhesive/silorane composite resin could not . The important role of adhesive system in fracture strength of the restored teeth was confirmed by these authors so that Single Bond as a filled adhesive is able to create a thick adhesive layer, acting as a stress absorbent . Furthermore, this layer resulted in more even distribution of stresses induced by polymerization shrinkage and load testing .…”
Section: Discussionmentioning
confidence: 77%
“…The lower marginal microleakage of SFRC Class II restoration compared to conventional composite (Z250) was reported by Garoushi et al; two types of composite resins were bonded using an etch‐and‐rinse adhesive . The low bonding efficiency of one‐step self‐etch (G‐aenial Bond) used along with SFRC in a study by Atalay et al was reported as a possible explanation for no significant difference between SFRC and other restorations in terms of fracture resistance …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The manufacturer recommends that the material will be capped with a traditional resin composite of approximately 2‐mm thickness because of its low strength and wear resistance. The reinforcing effect and gap/void formation of the flowable bulk‐fill material in ETT still remains unclear …”
Section: Introductionmentioning
confidence: 99%
“…The reinforcing effect and gap/void formation of the flowable bulk-fill material in ETT still remains unclear. 9,12 .…”
Section: Introductionmentioning
confidence: 99%